GENERATION OF SYNTHETIC RAINFALL DATA IN SEKAYAM SUB-WATERSHED BASED ON TRMM SATELLITE RAINFALL DATA CORRECTION EQUATION - Iwansyah, Iwansyah; Soeryamassoeka, SB.; Yulianto, Eko (Fakultas Teknik Universitas Tanjungpura, 2023)
The hydrological analysis is the first stage of the review in waterworks planning. Hydrological analysis necessitates the availability of sufficient data. Data availability tends to have several problems, including a lack of availability, incomplete/empty data, a smaller number of stations, observers, and observation systems, data entry that is still manual, and slow data collection. One possible solution is to use rain satellites. However, TRMM data must be evaluated for field suitability. TRMM (Tropical Rainfall Measurement Mission) rainfall data can help overcome this. TRMM is a NASA mission that uses weather monitoring satellite technology to monitor tropical rainfall. This is also the case for the Sekayam Subwatershed, part of the Kapuas River Basin.In the Sekayam sub-watershed, there are 14 (fourteen) rainfall observation stations managed by the Balai Wilayah Sungai Kalimantan (BWSK) I, but currently only 5 observation stations are still active, namely the SGU-01 Sanggau, SGU-03 Balai Karangan, SGU-06 Entikong, SGU-19 Semuntai and SC-01 Kembayan observation stations with data recorded up to 2019, while the other 9 (nine) observation stations do not have long continuous data, because there are years where rainfall data is not recorded. This is because the recording of rainfall on average stopped until 2005, or even some have stopped operating since the 1990s or early 2000s. This study aims to generate representative synthetic TRMM daily rainfall amount data for the Sekayam sub-watershed based on the correction equations obtained in a series of TRMM rainfall data validation analyses, so that it can be used as alternative daily rainfall data in water resources planning and management in the Sekayam sub-watershed. From the analysis, it can be seen that synthetic rainfall data in the Sekayam sub-watershed will be valid if it is generated with the linear model correction equation Y = 0.6708 X + 139.123 or can be interpreted as TRMM' = 0.6708 TRMM + 139.123.